The reading program reading for meaning - Mahony, David; Knowledge books and software (Brighton : Knowledge Books & Software, 2003)
This CD-ROM demonstrates techniques and strategies that can be employed to improve comprehension and retention skill, resulting in more efficient and enjoyable reading
System requirements: Standard Windows of Mac. Windows 95-98, Windows ME, NT 4.0, Windows XP. Web browser Ver. 4.0 or later IE or Netscape Java Script enables 486SX or Pentium CD_ROM double spin or better, 32MB RAM, VGA card set to min'High color 16 bit, 800 x 600', Mouse, Sound Card (optional)
Keywords: Reading; Special teaching methods